Über zweifache inhomogene Systeme von differentialgleischungen unendlicher Ordnung - Truschina, L. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. И. Tрушина. О двойной неоднородной системе дифференциальных уравнений бесконечного порядка L. Trušina. Begalinės eilės diferencialinių lygčių dvilypės sistemos